Colonic macrophage-targeted curcumin nanoparticles alleviate DSS-induced colitis in mice through the NF-kappa B pathway. (June 2021) - Liu, Gaodan; Feng, Simin; Sun, Yuxin; Wang, Dan; Shao, Ping; Sun, Peilong
Abstract: Oral targeted anti-inflammatory bioactive compounds released in the intestine to relieve the symptoms of ulcerative colitis have bacame a research hot spot. In this study, we investigated the colitis preventive effect of macrophage-targeted curcumin (Cur), which is encapsulated in chondroitin sulfate (CS) and zein (Z) based nanoparticles (NP). In vitro simulated digestion experiments revealed that Cur/CS/Z NP was more stable than Cur/Tre/Z NP (Cur/tremella polysaccharide/Z NP). Cytotoxicity, macrophage-targeting and colitis inhibiting effects of NP were investigated in both Raw 264.7 cells in vitro and DSS-induced colitis animal model in vivo . Compared with Cur/Tre/Z NP, Cur/CS/Z NP had stronger macrophage targeting effects. Both Cur/Z NP and Cur/CS/Z NP significantly ameliorated the symptoms of colitis by inhibiting the expression of COX-2, TNF-α, CSF-1, IL-1β and IL-6 through NF-κB pathway, while Cur/Z NP was less effective. These findings revealed that CS, as a targeted ligand of curcumin nanoparticles, enabled Cur/CS/Z NP to reach the colon and alleviated DSS-induced colitis in mice by inhibiting NF-κB activity. Graphical abstract: Image 1 Highlights: Cur/CS/Z NP had strong structural stability. After CS modification, Cur/CS/Z NP showed obvious macrophage targeting effect. Cur/CS/Z NP ameliorated colitis through NF-κB pathway.